Dynamic behavior analysis of radial hydraulically damped bushing based on FSI FEA method. (September 2020) - Li, Lin; Zeng, Xiangkun; Feng, Xiaolin
Abstract: Nonlinear dynamic performances of hydraulically damped bushings (HDBs) can be characterized with two terms, dynamic stiffness and loss angle. In this paper, dynamic characteristics of a RHDB are estimated based on FSI FEA methods. Dynamic performances of the RHDB by FSI FEA method are precise. Obviously, FSI FEA method proposed in this paper can be effectively used to investigate and optimize dynamic characteristics of a RHDB, and also further to solve FSI problems of other component with hydraulic damping properties in the design stage.